Assessment of higher mechanisation potential for Vietnamese pulpwood supply chains using sustainability indicators - Tran, V. T. (2017)
In Vietnam, planted forests are the main source of timber, providing about 4.8 million m3 of roundwood, which accounted for more than 70% of the domestic wood supply in 2009. However, most logging and extraction operations are still performed manually and by means of animal skidding, in rather poor working conditions. This study showed that the typical wood supply chain for pulpwood from planted forests on moderate slope (less than 30%) could be mechanised using suitable agricultural tractor–trailers to extract short logs from stump area to a landing accessible by large trucks to transport the logs to a mill for further processing. Higher level of mechanisation would lead to decrease of 15.3% in production costs, lower the directly involved employment from 13.90 to 4.26 hours m-3 as well as improve working and safety conditions for employees. However, mechanised system will create more heavily disturbed and impacted area in forest stands compared with manual and animal skidding methods if planning and supervision are not fully and carefully implemented